(untitled) (Research, Society and Development, 2022)
Corticosteroids and non-steroidal anti-inflammatory drugs are widely prescribed for oral surgery, but each has its own function. Therefore, this study aims to compare these two classes of drugs, observing where each is best applied, its indications and its effects in the face of oral surgery. This article refers to a narrative literature review, the articles used as reference were found through descriptors searched in PubMed, Google Scholar, SciELO and Portal BVS, in which of all articles searched, 21 articles were included for the preparation of the same. The literature describes that the use of corticosteroids is preemptively recommended to prevent edema, trismus and pain, however non-steroidal anti-inflammatory drugs are used postoperatively to obtain analgesia, also taking into account that the combined use of the two classes of drugs showed efficacy for preventive treatment of acute postoperative pain. Thus, it can be observed in this article that the corticosteroid class was better for use in the preoperative period, as there is a decrease in edema, trismus and pain, however, it can be concluded that the non-steroidal anti-inflammatory drug is favorable for its use in the preoperative period postoperative period to reduce or eliminate the pain that the patient may experience after surgery.